Myelination and Axonal Electrical Activity Modulate the Distribution and Motility of Mitochondria at CNS Nodes of Ranvier - Ohno, Nobuhiko (Society for Neuroscience, 2011)
Energy production presents a formidable challenge to axons as their mitochondria are synthesized and degraded in neuronal cell bodies. To meet the energy demands of nerve conduction, small mitochondria are transported to and enriched at mitochondrial stationary sites located throughout the axon. In this study, we investigated whether size and motility of mitochondria in small myelinated CNS axons are differentially regulated at nodes, and whether mitochondrial distribution and motility are modulated by axonal electrical activity. The size/volume of mitochondrial stationary sites was significantly larger in juxtaparanodal/internodal axoplasm than in nodal/paranodal axoplasm. With three-dimensional electron microscopy, we observed that axonal mitochondrial stationary sites were composed of multiple mitochondria of varying length, except at nodes where mitochondria were uniformly short and frequently absent altogether. Mitochondrial transport speed was significantly reduced in nodal axoplasm compared with internodal axoplasm. Increased axonal electrical activity decreased mitochondrial transport and increased the size of mitochondrial stationary sites in nodal/paranodal axoplasm. Decreased axonal electrical activity had the opposite effect. In cerebellar axons of the myelin-deficient rat, which contain voltage-gated Na(+) channel clusters but lack paranodal specializations, axonal mitochondrial motility and stationary site size were similar at Na(+) channel clusters and other axonal regions. These results demonstrate juxtaparanodal/internodal enrichment of stationary mitochondria and neuronal activity-dependent dynamic modulation of mitochondrial distribution and transport in nodal axoplasm. In addition, the modulation of mitochondrial distribution and motility requires oligodendrocyte–axon interactions at paranodal specializations.